Concentrations of sulphated estrone, estradiol and dehydroepiandrosterone measured by mass spectrometry in pregnant mares. (10th April 2019) - Legacki, E. L.; Scholtz, E. L.; Ball, B. A.; Esteller‐Vico, A.; Stanley, S. D.; Conley, A. J.
Summary: Background: Few studies have provided a longitudinal analysis of systemic concentrations of conjugated oestrogens (and androgens) throughout pregnancy in mares, and those only using immunoassay. The use of liquid chromatography tandem mass spectrometry (LC‐MS/MS) will provide more accurate concentrations of circulating conjugated steroids. Objectives: To characterise circulating concentrations of individual conjugated steroids throughout equine gestation by using LC‐MS/MS. Study design: Longitudinal study and comparison of pregnant mares treated with vehicle or letrozole in late gestation. Methods: Sulphated oestrogens and androgens were measured in mares throughout gestation and mares in late gestation (8–11 months) treated with vehicle or letrozole to inhibit oestrogen synthesis in late gestation. An analytical method was developed using LC‐MS/MS to evaluate sulphated estrone, estradiol, testosterone and dehydroepiandrosterone (DHEAS) during equine gestation. Results: Estrone sulphate concentrations peaked by week 26 at almost 60 μg/mL, 50‐fold higher than have been reported in studies using immunoassays. An increase in DHEAS was detected from 7 to 9 weeks of gestation, but concentrations remained consistently low (if detected) for the remainder of gestation and testosterone sulphate was undetectable at any stage. Estradiol sulphate concentrations were highly correlated with estrone sulphate but were a fraction of their level. Concentrations of both oestrogen sulphates decreased from their peak to parturition. Letrozole inhibited estrone and estradiol sulphate concentrations at 9.25 and 10.5 months of gestation but, no increase in DHEAS was observed. Main limitations: Limited number of mares sampled and available for analysis, lack of analysis of 5α‐reduced and B‐ring unsaturated steroids due to lack of available standards. Conclusions: Dependent on methods of extraction and chromatography, and the specificity of primary antisera, immunoassays may underestimate oestrogen conjugate concentrations in blood from pregnant mares and may detect androgen conjugates (neither testosterone sulphate nor DHEAS were detected here by LC‐MS/MS) that probably peak coincident with oestrogen conjugates between 6 and 7 months of equine gestation.